Gender and Occupational Outcomes: Longitudinal Assessments of Individual, Social, and Cultural Influences. 2008
DOI: 10.1037/11706-007
|View full text |Cite
|
Sign up to set email alerts
|

Is the desire for a family-flexible job keeping young women out of male-dominated occupations?

Abstract: Although women made tremendous gains in entering traditionally maledominated professions during the 20th century, gender differences have persisted through the turn of the millennium in adult occupational pursuits (National Center for Education Statistics [NCES], 2002). By the end of the 1990s, women were earning more bachelor's degrees than men but were still underrepresented in many traditionally male-dominated occupational fields, such as engineering (18%), physical science, (37%), mathematical and computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 46 publications
0
16
0
1
Order By: Relevance
“…Questions have also been raised concerning the validity and reliability of measures commonly used in this line of research, such as the person-thing construct and similar bipolar interest scales (e.g., data-ideas) (Tay et al 2011; Valian 2014). Further, although gender differences in work-life preferences are pervasive, they do not explain gender gaps in STEM interest or participation (Xie & Shauman 2003; Frome et al 2006, 2008; Cech et al 2011; Riegle-Crumb et al 2012; Perez-Felkner et al 2012; Morgan et al 2013; Mann & DiPrete 2013). …”
Section: Gender and Stem Educationmentioning
confidence: 99%
“…Questions have also been raised concerning the validity and reliability of measures commonly used in this line of research, such as the person-thing construct and similar bipolar interest scales (e.g., data-ideas) (Tay et al 2011; Valian 2014). Further, although gender differences in work-life preferences are pervasive, they do not explain gender gaps in STEM interest or participation (Xie & Shauman 2003; Frome et al 2006, 2008; Cech et al 2011; Riegle-Crumb et al 2012; Perez-Felkner et al 2012; Morgan et al 2013; Mann & DiPrete 2013). …”
Section: Gender and Stem Educationmentioning
confidence: 99%
“…Importantly, Weisgram and Diekman (in preparation) demonstrated that adolescents and emerging adults perceive STEM careers to afford family values less than other values such as money, power, and altruism. In their longitudinal work, Frome, Alfeld, Eccles, and Barber (2008) found that desiring a family flexible job in 12th grade predicted women changing their career aspiration from a masculine field to a feminine field by age 25.…”
Section: Integrating Communal Goal Processes With Other Frameworkmentioning
confidence: 99%
“…A complete examination of all of the constructs addressed in this model is beyond the scope of this paper, rather we focus on one of the primary constructs outlined by Eccles-values. In subsequent work, Eccles and colleagues broadened their original construct of subjective task value to include occupational values such as desiring a job that helps others, allows one to earn a high salary, or have time with his or her family (Eccles et al 1999;Frome et al 2008). The model posits that the values endorsed by males and females are directly influenced by the differential gender role expectations placed on these individuals by socializing agents.…”
Section: Introductionmentioning
confidence: 95%